2002
DOI: 10.1007/s00134-002-1398-z
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin: a marker to clearly differentiate systemic inflammatory response syndrome and sepsis in the critically ill patient?

Abstract: The definite differential diagnosis between SIRS and sepsis may not rely on a single application of procalcitonin but on the complete clinical and laboratory evaluation of the patient with procalcitonin playing a considerable role. Procalcitonin is an early prognostic marker of the advent of MODS; therefore, daily determinations might help in the follow-up of the critically ill patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(65 citation statements)
references
References 20 publications
6
54
1
3
Order By: Relevance
“…16,17 Moreover, many critically ill patients progressing to ARDS had serum procalcitonin levels Ն 10.0 ng/mL. 19 Similarly, the present study revealed that subjects with semi-quantitative serum procalcitonin levels Ն 10.0 ng/mL required intensive care, including vasopressor administration or mechanical ventilation, more frequently than those with levels of Ͻ 10.0 ng/mL. However, over one half of the subjects who required intensive care had semi-quantitative serum procalcitonin levels of Ͻ 10.0 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Moreover, many critically ill patients progressing to ARDS had serum procalcitonin levels Ն 10.0 ng/mL. 19 Similarly, the present study revealed that subjects with semi-quantitative serum procalcitonin levels Ն 10.0 ng/mL required intensive care, including vasopressor administration or mechanical ventilation, more frequently than those with levels of Ͻ 10.0 ng/mL. However, over one half of the subjects who required intensive care had semi-quantitative serum procalcitonin levels of Ͻ 10.0 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the prognostic role, studies showed that only one measurement of serum PCT at the onset of sepsis is not enough for predicting outcome, repeated measurements of serum values PCT being necessary. (14,15) A prospective study performed on 472 critically ill patients demonstrated that an increasing PCT value with >1.0 ng/mL after first reading is an independent predictor of mortality within 90 days and that mortality increased every day that PCT increased. (16) Another study showed that serum PCT values measured in day 2 after hospital admission discriminated between survivors and non-survivor patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…40 PCT was also found to be a predictor of mortality in a study involving 472 critical care patients. 41 PCT measurement was done daily in these patients and both high PCT levels and the increase in the levels following the first reading of greater then 1.0 ng/mL were independent predictors of 90 day mortality.…”
Section: Procalcitonin As a Prognostic Marker Of Bacterial Infectionsmentioning
confidence: 90%